Real-Time Prototype Electricity Monitoring and Forecasting System based on Wemos D1 R1 ESP8266 and IoT - Yudi Irawan Chandra; Irfan Irfan; Dian Gustina; Susi Wagiyati Purtiningrum; Nafisah Yuliani; Fahrul Nurzaman; Agus Wismo (Logistic and Operation Management Research (LOMR), 2023)
Technology helps people do things. IoT is a buzzword, but some need explanation. It means internet-connected devices. IoT seeks continuous internet benefits. Lighting, fans, automated doors. These things have internet-connected sensors. IoT technology allows internet-controlled household appliances. Internet-connected computers or smartphones monitor this tool. The purpose of this research is to create a system that can monitor the electric power in the room of the house in real-time through the Blynk application using a smartphone and make it easier for consumers to estimate the cost of electricity for a month. Systematics simplify and summarize this study. This study will use the Blynk smartphone app to monitor room electric power in real-time and anticipate monthly electricity expenses. Literature review expands research theories. Analysis and design, explaining the analysis based on the background and literature review, then constructing tools and designing the source code and workflow of the Wemos D1 R1 ESP8266 Microcontroller system. Implementation and testing discuss experimental results and how to test new technology. Study report analysis and development ideas conclude this section. This study produced a guide for designing IoT-based power monitoring device applications. Allow users to estimate their household electricity costs quickly and keep this option available. This research is limited by the Wemos ESP8266 D1 R1 microcontroller, INA219 current sensor, and LED for room lights. Wemos D1 R1 ESP8266 and IOT will be used to create a monitoring system tool and estimate electric power in real time using room fans. Future accomplishment. This method requires many components. This research may reveal how to lower electricity bills by monitoring and cuttingusage online.